2014
DOI: 10.1103/physrevb.89.125410
|View full text |Cite
|
Sign up to set email alerts
|

Broken symmetry induced band splitting in theAg2Gesurface alloy on Ag(111)

Abstract: We report a study of the atomic and electronic structures of the ordered Ag 2 Ge surface alloy containing ⅓ monolayer of Ge. Low-energy electron diffraction (LEED), scanning tunneling microscopy (STM), and angle-resolved photoelectron spectroscopy (ARPES) data reveal a symmetry breaking of the expected Ý3 × Ý3 periodicity, which is established for other Ag 2 M alloys (M = Bi, Sb, Pb, and Sn). The deviation from a simple Ý3 × Ý3 structure manifests itself as a splitting of diffraction spots in LEED, as a stripe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
8
16
1
Order By: Relevance
“…After germanium deposition at ∼200°C and the growth of the two-dimensional phases, as displayed in figure 1, the total Au 4f intensity at normal emission is reduced by ∼32%; still, a fraction of the Au in extremely surface sensitive conditions (escape depth estimated at ∼0.4 nm), essentially signaling a unique environment of the germanium atoms at the very top surface and their metallic character; we assign the small broad additional component (just 9% of the total intensity) at normal emission to defect sites. The essentially unique Ge species indicate that no formation of a surface alloy occurs, at variance with the Ag 2 Ge one formed in the case of Ge deposited on Ag(111) surfaces [9,11] or the one initially formed upon Ge deposition onto the Au(110) surface [27]. In this respect, we note that the formation of a surface alloy is surface dependent; typically, it takes place upon Ge deposition onto the Ag(111) surface, but not onto the Ag(110) and Ag(100) ones.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…After germanium deposition at ∼200°C and the growth of the two-dimensional phases, as displayed in figure 1, the total Au 4f intensity at normal emission is reduced by ∼32%; still, a fraction of the Au in extremely surface sensitive conditions (escape depth estimated at ∼0.4 nm), essentially signaling a unique environment of the germanium atoms at the very top surface and their metallic character; we assign the small broad additional component (just 9% of the total intensity) at normal emission to defect sites. The essentially unique Ge species indicate that no formation of a surface alloy occurs, at variance with the Ag 2 Ge one formed in the case of Ge deposited on Ag(111) surfaces [9,11] or the one initially formed upon Ge deposition onto the Au(110) surface [27]. In this respect, we note that the formation of a surface alloy is surface dependent; typically, it takes place upon Ge deposition onto the Ag(111) surface, but not onto the Ag(110) and Ag(100) ones.…”
Section: Resultsmentioning
confidence: 94%
“…However, to the best of our knowledge, this has failed up to now, because (1) the 'magic mismatch' between three lattice constants of silicene and four of the Ag(111) plane is not fulfilled for germanene, and (2) germanium most probably prefers to form an ordered Ag 2 Ge surface alloy, where Ge atoms, up to a coverage of one-third of a monolayer (1/3 ML), substitute Ag ones at the silver surface. This surface alloy presents a complex '√3 × √3' structure [9], which not only deviates in its geometry but also in its electronic properties [9,10] from the simple √3 × √3 reconstruction envisaged earlier [11].…”
Section: Introductionmentioning
confidence: 97%
“…As a typical metalloid element in group IV, germanium (Ge) only takes on a diamond structure with sp 3 hybridization of the valence electrons in bulk form, similar to C and Si in their bulk crystals 26 . Very recently, it was reported that the 2D allotrope of Ge, germanene, had been successfully epitaxially grown on MoS 2 27 and metallic substrates [28][29][30][31][32][33][34][35][36] , including Au(111) [30][31][32] , Pt(111) 33 , Al(111) 34,35 and Cu(111) 36 surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, Ag 2 Ge alloy has been observed by low-energy electron diffraction (LEED) and reflective high-energy electron diffraction (RHEED) measurements after deposition of Ge atoms on Ag(111). 26,37,38 Unexpected surface band splitting behavior at the M points of the Brillouin zone (BZ) in Ag 2 Ge alloy was reported, which is attributed to its novel atomic structure, where a striped appearance is induced by the long-range √3×6√3 modulation. 26,38 These preliminary reports suggest that the interaction between Ag surfaces is very much needed to illustrate these issues.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry as well as properties of single‐layer germanene deposited on the metal surfaces deviate due to the strong germanene‐substrate interaction. Alloy formation has been observed with some of these substrates such as Pt, and Ag . Thus, the experimental realization of germanene with a weakly interacting substrate is crucial.…”
Section: Synthesis Structure and Propertymentioning
confidence: 99%